Exploring Teens Perception of Health Protocols During COVID-19: A Case Study of Chakdara KPK Pakistan (Journal of Asian Development Studies, 2025)
This cross-sectional study investigates the perspectives of 200 teenagers (aged 13–18) in Chakdara, Dir Lower, regarding the effectiveness of COVID-19 SOPs implemented by the Government of Pakistan. Using a self-administered questionnaire based on the WHO’s Secondary Structure Survey Model, data was collected from various institutions over six months through convenience sampling. Among the participants, 60.7% were male and 39.3% female, with the majority holding either Matric or FSc qualifications. Findings revealed that 84% of the teenagers did not support government-implemented SOPs, while only 16% were in favor. Statistical analysis indicated no significant association between gender and attitudes toward SOPs; however, a notable relationship was found between educational level and SOP perception. Males scored higher than females in their perception of COVID-19-related issues and internet use. These findings highlight a general skepticism among adolescents toward pandemic measures, emphasizing the need for targeted awareness campaigns to improve compliance and public health outcomes among youth.